(3QSGdI aj TQM bhd GdcfR (B" (3hbVi QcYJjf hdh Zhi CQHYkG (B"s - (3CMeO Hf eUWai GdMfajs; (3YHO Gddg Hf CMeO Hf eMehO GdfSaj, CHh GdHQcGJ, MGaX GdOjf,J (B710 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHg fSJYjf bGd GdTjN GdYGde GdYdGeI CHh GdHQcGJ YHO Gddg Hf CMeO Hf eMehO GdfSai QMeg Gddg JYGdi ai cJGHg GdeSei HcfR GdObGFb HGH GdhJQ hGdfhGad s
(3BNQgG (B:s
(3hgPG gh GdbjGS dCf cd UdGI QcYJjf ef Gdfad UdGI Ydi MOg hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B32s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3Gdabg GdMfajs